New Experimental Tools to Use Noble Gases as Artificial Tracers for Groundwater Flow - Brennwald, Matthias S.; Peel, Morgan; Blanc, Théo; Tomonaga, Yama; Kipfer, Rolf; Brunner, Philip; Hunkeler, Daniel (Frontiers in Water, 2022)
Labelling groundwater by injecting an artificial tracer is a standard and widely used method to study groundwater flow systems. Noble gases dissolved in groundwater are potentially ideal artificial tracers, as they are not subject to biogeochemical transformations, do not adsorb onto the aquifer matrix, are colourless, and have no negative impact on the quality of groundwater resources. In addition, combining different noble-gas species in multi-tracer tests would allow direct analysis of the spatio-temporal heterogeneity of groundwater flow systems. However, while the handling of noble gases is safe and straightforward for injection into groundwater, conventional methods to analyse dissolved noble gases tend to be impractical for groundwater tracer tests. The sampling and subsequent lab-based analysis of dissolved noble gases are laborious, expensive and time intensive. Therefore, only researchers with access to specialised noble-gas labs have attempted such tracer tests. The recently developed gas-equilibrium membrane-inlet mass spectrometers (GE-MIMS) allow efficient on-site analysis of dissolved gases at high temporal resolution. The GE-MIMS instruments thereby eliminate most of the analytical and logistical constraints of conventional lab-based techniques and therefore provide new opportunities for groundwater tests using artificially injected gases. We used a GE-MIMS to systematically test the applicability of He, Kr and Xe as artificial groundwater tracers. These gas species were injected into groundwater as Dirac-like pulses at three piezometers located at various locations upstream of a pumping well, where dissolved gas concentrations were continuously monitored with the GE-MIMS instrument. The groundwater travel times observed in these tracer tests ranged from a few hours to several weeks, and were consistent with the groundwater flow field at the experimental test site. Travel times determined from the noble gas tracer tests were also consistent with those obtained with traditional dye tracers.